2017
DOI: 10.1016/j.redox.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and oxidative stress in the perinatal period

Abstract: Fetal life evolves in a hypoxic environment. Changes in the oxygen content in utero caused by conditions such as pre-eclampsia or type I diabetes or by oxygen supplementation to the mother lead to increased free radical production and correlate with perinatal outcomes.In the fetal-to-neonatal transition asphyxia is characterized by intermittent periods of hypoxia ischemia that may evolve to hypoxic ischemic encephalopathy associated with neurocognitive, motor, and neurosensorial impairment. Free radicals gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
165
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(172 citation statements)
references
References 85 publications
2
165
1
4
Order By: Relevance
“…[38, 39] In animal models, even a brief exposure to 100% O 2 results in very high PaO2 levels in the brain and other tissues. [40, 41] Further, multiple animal and human studies have found adverse effects of hyperoxemia during resuscitation resulting in tissue injury and worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[38, 39] In animal models, even a brief exposure to 100% O 2 results in very high PaO2 levels in the brain and other tissues. [40, 41] Further, multiple animal and human studies have found adverse effects of hyperoxemia during resuscitation resulting in tissue injury and worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In case of iron overloading or severe oxidative stress, the antioxidant defense capacity is exceeded, making nontransferrin bonds available, with the release of low molecular mass iron, followed by lipid peroxidation. This may occur even if transferrin is not completely iron saturated [42].…”
Section: Effects Of Oxidative Stress In Neonatal Asphyxia and Hypoxicmentioning
confidence: 99%
“…In the reoxygenation stage, hypoxanthine is converted to uric acid under the action of xanthine oxidase, and superoxide and peroxide are released through the mediation of xanthine oxidase by molecular oxygen binding. Hydroxyl radical generated through the Fenton reaction will also be released, due to the catalytic effect of metals such as iron [42]. Perinatal hypoxic stress is a frequent cause of morbidity, mortality, and neurological damage in survivors.…”
Section: Effects Of Oxidative Stress In Neonatal Asphyxia and Hypoxicmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuron viability is intimately reliant on a continuous blood-borne supply of both oxygen and glucose to avoid ATP exhaustion and subsequently cells swelling, apoptosis, and necrosis [2, 3]. …”
Section: Introductionmentioning
confidence: 99%